The Role of Hardiness and Moral Intelligence in Predicting the Anxiety of Corona Disease in Students - Jafari, Esa; Razaghilord, Ghasem; Khoshtinat, Valiollah; Poormohseni, Fereshte; Rahmanian, Mahdieh (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: The present study investigated the role of hardiness and moral intelligence in Corona disease anxiety in middle school male students of Khalkhal City. Materials and Methods: This research was descriptive-correlational. The statistical population was all male secondary school students of Khalkhal City in the academic year 2019-2020, and a sample of 265 students was selected using the cluster random sampling method. Alipour et al.'s Corona Disease Anxiety Scale, Lennick and Keil's Moral Intelligence Questionnaire, and Kobasa's Hardiness Scale were used to collect data. The data were analyzed using the Pearson correlation coefficient and Multiple regression analysis in SPSS software version 26. Results: The findings showed that there is an inverse and significant relationship between predictors of hardiness (r=-321) and moral intelligence (r=-668) with the criterion variable of Corona disease anxiety (P<0.001). Also, the results of multiple regression analysis showed that the predictor variables of hardiness and moral intelligence explained a total of 0.56 of the changes in the anxiety variable of Corona disease. Conclusion: In conclusion, increasing students' resilience and moral intelligence could reduce their anxiety about coronary disease. According to the results of the research, we can state that teachers and managers of educational centers can hold workshops focusing on teaching hardiness and moral intelligence in order to reduce anxiety in these people and improve their level of mental health.